Difference in the Number of Germs Before and After Hand Washing with Triclosan dan Cida-stat® Antiseptic An Experimental Study on Hand Washing of Nurses at Sultan Agung Islamic Hospital - Abduh, M. Saugi (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2010)
Background:a study conducted among 11 hospitals in DKI Jakarta in 2004 showed that 9.8% in-patient had nosocomial infections, the most common way in which germs spread is through personnel’s hands. Thus, hand washing and antiseptics play a significant role in the prevention of nosocomial infections Triclosan and Cidastat are the two antiseptics used in the Sultan Agung Islamic Hospital. The purpose of this study was to find out the difference in the number of germs on nurse’s hands using Triclosan and Cida-stat.Design and Method: This experimental study using pre and post test control group design used three treated groups; group A (treated with aquabidest), group B (treated with Triclosan), Group C (treated with Cidastat). The samples were palms of 12 nurses for in-patients in the Baitul Syifa ward and Arrijal of Sultan Agung Islamic Hospital.Result: One way anova showed a statistically significant different among the three treated groups with p value of 0.020 (<0.05). Post Hoct Test to compare the number of germs before and after hand washing using Triclosan and Cida-stat resulted in no significant difference (>0.05). The paired T test showed a significant difference between Triclosan and Cidastat group.Conclusion: There was no significant different in the number of germ before and after hand washing using Triclosan and Cida-stat antiseptics (Sains Medika, 2(2):163-169).